The relationship between blood lactate levels and mortality in pediatric intensive care patients. Issue 3 (2013) - Yolbaş, İlyas and Şen, Velat and Boşnak, Mehmet and Kelekçi, Selvi and Yel, Servet and Güneş, Ali
No abstract available